2021
DOI: 10.3390/ijms22115754
|View full text |Cite
|
Sign up to set email alerts
|

The Involvement of Ubiquitination Machinery in Cell Cycle Regulation and Cancer Progression

Abstract: The cell cycle is a collection of events by which cellular components such as genetic materials and cytoplasmic components are accurately divided into two daughter cells. The cell-cycle transition is primarily driven by the activation of cyclin-dependent kinases (CDKs), the activities of which are regulated by the ubiquitin-mediated proteolysis of key regulators such as cyclins and CDK inhibitors (CKIs). Thus, the ubiquitin-proteasome system (UPS) plays a pivotal role in the regulation of the cell-cycle proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 236 publications
(284 reference statements)
0
47
0
Order By: Relevance
“…A majority of intracellular proteins are modified by ubiquitination ( Amm et al, 2014 ). Several Ub signals are recognized by proteasomes, thereby serving as a regulatory mechanism for protein degradation, affecting nearly all aspects of cellular processes ( Chowdhury and Enenkel, 2015 ; Hanna et al, 2019 ; Sakai et al, 2020 ; Fhu and Ali, 2021 ; Goetzke et al, 2021 ; Qu et al, 2021 ; Zou and Lin, 2021 ). Ubiquitin signaling is strictly regulated by a multistep cascade reaction consisting of three enzyme groups.…”
Section: Introductionmentioning
confidence: 99%
“…A majority of intracellular proteins are modified by ubiquitination ( Amm et al, 2014 ). Several Ub signals are recognized by proteasomes, thereby serving as a regulatory mechanism for protein degradation, affecting nearly all aspects of cellular processes ( Chowdhury and Enenkel, 2015 ; Hanna et al, 2019 ; Sakai et al, 2020 ; Fhu and Ali, 2021 ; Goetzke et al, 2021 ; Qu et al, 2021 ; Zou and Lin, 2021 ). Ubiquitin signaling is strictly regulated by a multistep cascade reaction consisting of three enzyme groups.…”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs are central regulators of biological events. And ubiquitin–proteasome systems are also involved in almost all cell signaling regulation such as cell cycle, cell proliferation, apoptosis, and autophagy [ 163 , 164 , 165 ]. Here, we illustrate the important impact of crosstalk between miRNA and UPS in autophagy regulation due to the increasingly important impact status of autophagy in malignant diseases such as tumors today.…”
Section: Discussionmentioning
confidence: 99%
“…Three of the seven β-subunits are catalytically active and provide proteolytic activity of the proteasome: β1-subunit has caspase-like activity (CL), β2-subunit has trypsin-like activity (TL), and β5-subunit demonstrates chymotrypsinlike activity (ChTL) [3,4]. Dysfunction of this complex can lead to regulatory proteins be stabilized due to reduced degradation or lost due to accelerated degradation [5]. Previous research has shown that tissue proteasome activity is associated with cancer progression and can be used to stratify risk [6,7].…”
Section: Introductionmentioning
confidence: 99%